IMPLEMENTASI QUANTUM LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA SISWA KELAS V SDN PEDURUNGAN KIDUL 02 SEMARANG - Ikha Listyarini (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstract: This research is motivated by the students who still have difficulties in understanding the subject matter taught especially on the subjects of Indonesian Language and still not maximally in the mastery of the concept, the teachers only rely on books and teaching materials from the government so that they can not develop the learning process in the classroom. The problem in this research is whether the application of Quantum Learning in Indonesian Language subjects can improve the achievement of students of grade V SD Pedurungan Kidul 02 Semarang. Results Improved learning completeness before and after learning by applying quantum Learning can be seen by the calculation of gain scores. Gain obtained in the research shows that the pretest used is the result of learning on the pre cycle while the postest is the result of cycle II. The number of pre-cycle values 2592 and the number of cycles of II 3276. While the average value on the pre cycle is 65% and the average value in cycle II is 81.9%. The N-gain obtained from pretest and postest is 0.475% by using the normalized gain formula, the N-gain analysis on pretest and posttest shows 8 students in the high category ie at g0 0, 7 and 27 student interval in medium category ie at interval gain 0.3≤g <0.7 and 5 students in the low category that is at g <0.3. From that category the N-gain results fall into the moderate category within the gain interval of 0.3 ≤ g <0.7. The data is supported by an increase in student activity showing from cycle 1 63% and on cycle II 87%. And also strengthened from the data attitudes of discipline obtained in 40 students the number of cycles I is 817 with 81.7% percentage and on the second cycle the number of scores obtained is 885 with 88.5% percentage.